Molecular Mechanisms of Action of Functional Foods and Nutraceuticals for Chronic Diseases: Volume II - Abdollahi, Shima; Mohan, Syam; Pathak, Yashwant V (Nutraceuticals, 2023)
There has been a global rise in the incidence of chronic illnesses, which may be partially attributed to the lengthening of the average human lifespan. Functional foods and nutraceuticals can potentially play a role in the development and maintenance of health. They can assist the body in its battle against inflammation and chronic illnesses. Molecular Mechanisms of Action of Functional Foods and Nutraceuticals for Chronic Diseases addresses the effects and mechanism of functional foods in relation to chronic diseases such as obesity, cardiovascular diseases, diabetes, cancer, etc. This volume, like the first volume, Applications of Functional Foods and Nutraceuticals for Chronic Diseases, inspires new thought processes and a paradigm shift in research and development. Key Features: Discusses the molecular mechanism of action, the range of toxicities exerted by these food components for functional foods for addressing chronic conditions Enhances scientists' and industrial personnel's knowledge of functional foods and in the management of chronic diseases Presents research on the role of functional foods/nutraceuticals in preventing and treating chronic diseases through epigenetic modulation. Explores various subjects such as epigenetics, immunological, metabolic, technological, and neurodegenerative aspects affected by functional foods in chronic diseases The world's leading wellness centers for chronic diseases are using functional foods and nutraceuticals in their practice and discovering their useful applications, and this second of two volume set is another great reference for practitioners, scientists, and clinicians in the management of chronic diseases. Contributors hail from different geographical locations around the world and have many years of research and scholarly experience in functional foods, nutraceuticals, and biology.